2003
DOI: 10.1163/156853003322796073
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Wilderness: The Work of Wilderness Officers

Abstract: Ideologies having roots in the legal structure of the system of wildlife protection characterize the work culture of the Pennsylvania wilderness of cer. This paper examines these ideologies and the characteristically strong social solidarity of the community of wilderness of cers. Wilderness of cers are both law enforcement agents and conservationists. They mediate between human and animal as well as between what is considered scienti c management and what is considered unenlightened and even lawless behavior.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Prior research has found that not only are the enforcement of natural resources laws an important part of their work, but that more traditional policing tasks are increasing for conservation officers (Falcone, 2004). Beyond law enforcement, conservation officers must also make efforts to mitigate human–wildlife conflict, provide habitat consultations to landowners, assist in hunter safety programs and provide outreach to special interest groups (Lawson, 2003; Rossler and Suttmoeller, 2021). This especially broad role may highlight the value added to conservation police for increased educational and training standards in their recruitment process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research has found that not only are the enforcement of natural resources laws an important part of their work, but that more traditional policing tasks are increasing for conservation officers (Falcone, 2004). Beyond law enforcement, conservation officers must also make efforts to mitigate human–wildlife conflict, provide habitat consultations to landowners, assist in hunter safety programs and provide outreach to special interest groups (Lawson, 2003; Rossler and Suttmoeller, 2021). This especially broad role may highlight the value added to conservation police for increased educational and training standards in their recruitment process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The exception seems to be the occupation of game warden and the crime of poaching which has received scholarly attention (Carter, 2004(Carter, , 2006Dizard, 2003;Forsyth, 1993aForsyth, , 1993bForsyth, , 1994Forsyth, , 2008Forsyth & Forsyth, 2009, 2010Forsyth & Marckese, 1993a, 1993bForsyth, Gramling & Wooddell, 1998;Hampshire, Bell, Wallace & Stepukonis, 2004;Jacoby, 2001;Lawson, 2002Lawson, , 2003McMullan & Perrier, 2002;Sherblom, Keranen & Withers, 2002). Their job is dangerous with wardens getting killed and assaulted on the job.…”
Section: Rural/urban Drug Use and Crimementioning
confidence: 99%
“…The data revealed excuses and justifications for poacher behavior. Other research has focused on describing the work of game wardens regarding fisheries (Hampshire et al 2004;McMullan and Perrier 2002), general job descriptions (Lawson 2002(Lawson , 2003Tobias 1998); the changing nature of the job (Sherblom et al 2002) and historical studies of the work of game wardens (Jacoby 2001). While all work on game wardens and poachers implicitly focus on the dangers of the job, only Carter (2004), Forsyth (1993b, Palmer and Bryant (1985) and Walsh and Donovan (1984) contain data on the dangers of the work of game wardens.…”
Section: Introductionmentioning
confidence: 99%